Mechanisms and initiatives of corporate social responsibility behaviours in Ghana: a co-integration approach - Emmanuel Opoku Marfo (Cogent Business & Management, 2024)
This study examined the effects of corporate social responsibility (CSR) behaviours, mechanisms, and initiatives on the involvement of mining companies in Ghana. Longitudinal data was collected from the Ghana Chamber of Mines and Industry between 2012 to 2022. Using a co-integration approach, the study examines the relationship between various factors and CSR engagement in the Ghanaian context. The study adopted a probabilistic model to measure the robustness of CSR behaviour on CSR mechanisms and initiatives. However, no positive correlation existed between partnerships and CSR engagement, implying that any discrepancy could be attributed to contextual factors in the studied industries. While this study identifies a negative relationship with partnerships, it also highlights the positive impact of voluntary programmes on CSR engagements. Therefore, it is recommended that aligning CSR initiatives with appropriate mechanisms would enable companies to effectively and efficiently pursue their CSR objectives since CSR is integral to modern business practices.
Keywords: 650; Co-integration; CSR behaviour; CSR mechanisms and initiatives; Ghana